The Effect of Self-Confidence on Students' Understanding of Mathematical Concepts through the Implementation of the Independent Curriculum - Gita Andriani, Desi (Noumerico: Journal of Technology in Mathematics Education, 2023)
This study aims to determine the effect of self-confidence has a positive effect on students' understanding of mathematical concepts through the implementation of an independent curriculum. This study used a quantitative approach with an ex-post facto research design. The population in this study consisted of all students at Wahidiyah Kediri Junior High School, consisting of 447 students. The sampling technique used purposive sampling technique and obtained a sample of 96 students. The instruments used were a self-confidence questionnaire and an understanding test of mathematical concepts. Data analysis used in this study used simple linear regression whose calculations were assisted by the SPSS v.25 application for windows. The results of this study indicate that self-confidence has a positive effect on students' understanding of mathematical concepts through the implementation of an independent curriculum, with a significant value of 0.000 <0.05 and a coefficient of determination of 91.2%